Haemodiafiltration at increased plasma ionic strength for improved protein‐bound toxin removal. (22nd June 2016) - Krieter, D. H.; Devine, E.; Körner, T.; Rüth, M.; Wanner, C.; Raine, M.; Jankowski, J.; Lemke, H.‐D.
Abstract: Aim: Protein‐bound uraemic toxin accumulation causes uraemia‐associated cardiovascular morbidity. Enhancing the plasma ionic strength releases toxins from protein binding and makes them available for removal during dialysis. This concept was implemented through high sodium concentrations ([Na + ]) in the substituate of pre‐dilution haemodiafiltration at increased plasma ionic strength (HDF‐IPIS). Methods: Ex vivo HDF‐IPIS with blood tested increasing [Na + ] to demonstrate efficacy and haemocompatibility. Haemocompatibility was further assessed in sheep using two different HDF‐IPIS set‐ups and [Na + ] between 350 and 600 mmol L −1 . Safety and efficacy of para‐cresyl sulphate (pCS) and indoxyl sulphate (IS) removal was further investigated in a randomized clinical pilot trial comparing HDF‐IPIS to HD and HDF. Results: Compared to [Na + ] of 150 mmol L −1, ex vivo HDF‐IPIS at 500 mmol L −1 demonstrated up to 50% higher IS removal. Haemolysis in sheep was low even at [Na + ] of 600 mmol L −1 (free Hb 0.016 ± 0.001 g dL −1 ). In patients, compared to HD, a [Na + ] of 240 mmol L −1 in HDF‐IPIS resulted in 40% greater reduction (48.7 ± 23.6 vs. 67.8 ± 7.9%; P = 0.013) in free IS. Compared to HD and HDF (23.0 ± 14.8 and 25.4 ± 10.5 mL min −1 ), the dialytic clearance of free IS was 31.6 ± 12.8 mL min −1 ( P = 0.017) in HDF‐IPIS, but [Na + ] in arterial blood increased from 132 ± 2 to 136 ± 3 mmol L −1 (0 vs. 240 min; P < 0.001). Conclusion: HDF‐IPIS is technically and clinically feasible. More effective HDF‐IPIS requires higher temporary plasma [Na + ], but dialysate [Na + ] has to be appropriately adapted to avoid sodium accumulation.